Efeitos da adição do IGF-1 ou IGF-LongR3 sobre aspectos celulares e moleculares de complexos cumulus-oócito durante a maturação oocitária in vitro em bovinos - Araujo, Michelle Silva [UNESP] (2015)
The insuline like growth factor-1 recombinant-3 (LongR3-IGF-1) a synthetic analogue of IGF-1 with greater bioavailability has not yet been used in in vitro maturation medium of cumulus-oocyte complexes (COCs). Therefore the aim of this study was to evaluate and compare the effects of LongR3-IGF-1 and insulin-like growth factor-1 (IGF-1) addition in the IVM of bovine oocytes on meiotic progression, apoptosis, and genic expression COCs (GDF9, BMP15, BAX, BCL2, OOSP1, IGFBP2, IGBFP4 e IGFBP5) and their respectively cumulus cells (AREG, EGFR, FSHR, COX2, BAX, BCL2, IGFBP2, IGFBP4 e IGFBP5). Bovine ovaries were collected in slaughterhouse being selected 739 oocytes after aspiration of follicles from 2-8mm diameter. In vitro maturation (IVM) was performed on basic maturation medium containing IGF-1 (100 ng/ml), LongR3-IGF-1 (100ng/ml), and two control groups: 0.1% polyvinyl alcohol (PVA) or 10% fetal bovine serum (FBS), for 22-24 hours in an incubator at 38.5°C and 5% CO2. Subsequently oocytes were denuded and prepared for TUNEL technique, staining Hoechst 33342 and RT-qPCR, intending to evaluate apoptosis, nuclear maturation and gene expression, respectively. Statistical analysis was performed using a linear mixed effects model, which correlated the change in metaphase stage 1 to 2 and the absence of apoptosis among the experimental groups. ANOVA and Tukey tests were used to analyze the results obtained by RTqPCR. After ten replicas of IVM, 339 oocytes (n=5 pools) were evaluated for meiotic progression and apoptosis and 400 (n=5 pools) for gene expression. There was no statistical difference (P>0,05) between the experimental groups with respect to meiotic progression and apoptosis. It was possible to detect mRNA expression of all evaluated genes in the oocyte and its cumulus cells in all experimental groups. There was statistical difference between the group 10% FBS and IGF-1 and LongR3-IGF-1 groups for the expression of gene IGFBP4 in ...